Biological water at the protein surface: Dynamical solvation probed directly with femtosecond resolution - Pal, Samir Kumar (The National Academy of Sciences, 2002)
Biological water at the interface of proteins is critical to their equilibrium structures and enzyme function and to phenomena such as molecular recognition and protein–protein interactions. To actually probe the dynamics of water structure at the surface, we must examine the protein itself, without disrupting the native structure, and the ultrafast elementary processes of hydration. Here we report direct study, with femtosecond resolution, of the dynamics of hydration at the surface of the enzyme protein Subtilisin Carlsberg, whose single Trp residue (Trp-113) was used as an intrinsic biological fluorescent probe. For the protein, we observed two well separated dynamical solvation times, 0.8 ps and 38 ps, whereas in bulk water, we obtained 180 fs and 1.1 ps. We also studied a covalently bonded probe at a separation of ≈7 Å and observed the near disappearance of the 38-ps component, with solvation being practically complete in (time constant) 1.5 ps. The degree of rigidity of the probe (anisotropy decay) and of the water environment (protein vs. micelle) was also studied. These results show that hydration at the surface is a dynamical process with two general types of trajectories, those that result from weak interactions with the selected surface site, giving rise to bulk-type solvation (≈1 ps), and those that have a stronger interaction, enough to define a rigid water structure, with a solvation time of 38 ps, much slower than that of the bulk. At a distance of ≈7 Å from the surface, essentially all trajectories are bulk-type. The theoretical framework for these observations is discussed.